Exploring the position of curriculum studies across the continuum of teacher education in Ireland. Issue 4 (2nd October 2017) - Lynch, Raymond; McCormack, Orla; Hennessy, Jennifer
Abstract : Curriculum, while often narrowly defined, is a contested space that stimulates continuing international debate, yet the importance of curriculum studies is frequently overlooked across the continuum of teacher education. Within the Irish context a technicist interpretation of curriculum studies, focusing primarily of subject knowledge and development, has historically been adopted. More recent Teaching Council of Ireland policy documents have espoused a broader macro understanding of curriculum studies as a foundation discipline within initial teacher education. However, concerns have been raised regarding student teachers' ability to fully engage with such material so early in their professional development. With the recently embraced continuum of teacher education in Ireland, this paper examines how curriculum studies is currently defined by Irish policy and problematises how it is addressed in practice. The paper proceeds to explore emerging opportunities to expand this area of study across the continuum. A case for the place of curriculum studies as central to the advancement of the profession through the promotion of teachers as change agents is presented.